Reciprocal Teaching: An Instructional Strategy to Enhance English Reading Comprehension of Secondary School Students - Ruangprasertkun, Patsachon; Chinwonno, Apasara (An Online Journal of Education, 2023)
Reciprocal Teaching has become an instructional strategy to enhance English reading comprehension for Thai secondary school students. Forty students participated in this mixed-methods study for ten weeks. The study compared students’ English reading comprehension in Reciprocal Teaching with those students in pre, while, and post-Reading Instruction. It also explored students’ perceptions of Reciprocal Teaching strategies. The research instruments included (1) an English reading comprehension test; (2) a Reciprocal Teaching questionnaire, and (3) a Semi-structured interview. Quantitative data from a paired samples t-test indicated that students in the Reciprocal Teaching significantly improved their English reading comprehension at a level of 0.05. The qualitative data showed positive perceptions toward Reciprocal Teaching strategies, including predicting, clarifying, questioning, and summarizing. This study led to the application of Reciprocal Teaching to support students reading English in a foreign language.